Percutaneous collagen induction as an additive treatment for scar formation following thermal injuries: preliminary experience in 47 children - Kubiak, Rainer; Lange, Bettina (Burns, 2017)
Background: Thermal injuries are one of the most physically and psychologically devastating causes of pediatric trauma. Post-traumatic sequelae such as hypertrophic scars and contractures often result in long lasting morbidity and disfigurement. Conservative therapy, including pressure garments and silicone, is the gold standard for scar management in the pediatric population. Most recently percutaneous collagen induction (PCI) was introduced as an alternative treatment in adults. The aim of this report was to share our experience with PCI in children and adolescents in scar management following thermal injuries. Patients and methods: Between July 2013 and February 2016, a total of 99 PCI treatments were performed on forty-seven children and adolescents for scar formation following thermal injuries in this retrospective study. A medical roller device (Dermaroller®, Dermaroller GmbH, Wolfenbüttel, Germany) with 2.5mm long needles was used. All procedures were carried out under general anesthesia. At the end of the operation vitamin A and vitamin C oil (ENVIRON® AVST Body Oil; Environ Skin Care, Pty. Ltd., Cape Town, South Africa) was applied topically. Photographs were taken before and a minimum of 4 weeks after the first PCI in order to document the effect on scar tissue. These images were graded according to the Vancouver Scar Scale (VSS). Results: The median age at the time of the first PCI was 8.3 years (range, 0.8-21.2 years). The median time interval between the injury and PCI was 18 months (range, 4-170 months). There were no intraoperative problems noted. Minor postoperative complications occurred in 2 patients (4.3%). All patients reported subjective improvement and were satisfied with the procedure and the results. Pre- and post-treatment photographs were available in 40 patients, and overall VSS scores improved post-treatment in all patients. Following a single PCI treatment, scar vascularity, pliability and height all improved, however there was no statistically significant effect on pigmentation. Conclusions: PCI is an enrichment of the armamentarium for scar treatment following thermal injuries in children and adolescents. Further prospective studies are recommended regarding the optimal timing for this treatment and long term outcome in the pediatric population.
Gesehen am 05.11.2018